The role of hormones during Equine-Assisted Activity and Therapy: a literature review - Adriana Ferlazzo (Accademia Peloritana dei Pericolanti, 2021)
Recent acquisitions on human-animal interaction and on its use in complementary medicine are reported. The contribution of horses to one health concept and the effects of equine-assisted activity and therapy (EAAT) are evaluated, also in the light of need to monitor stress conditions in therapeutic horses. The role of hypothalamus-pituitary-adrenal axis’ hormones and of total and free iodothyronines in stress coping of horses during therapeutic riding is critically discussed